Verification of quartz crystal microbalance array using vector network analyzer and openQCM - Zainuddin, Ahmad Anwar; Nordin, Anis Nurashikin; Ab Rahim, Rosminazuin; Md Ralib @ Md Raghib, Aliza 'Aini; Khan, Sheroz; Guines, Cyril; Chatras, Matthieu; Pothier, Arnaud (Institute of Advanced Engineering and Science (IAES), 2018)
Quartz Crystal Microbalance (QCM) is a device that allows non-destructive measurements of r in situ reaction activities. In this article, an array comprising of six 3MHz QCM sensors in an array were characterized using a vector network analyzer and OpenQCM, a portable measuring instrument that measures change in resonance frequency. Measurements of S21 transmission characteristics using the vector network analyzer provides the resonance frequency and can also be used to derive the RLC equivalent electrical circuit values of a resonant two-port network based on the Butterworth-Van Dyke model. In this work, Rm, Lm, Cm and Co were obtained via curve-fitting of the measurement results to the simulated results. Measurements were done in triplicates to verify reproducibility for all 6 sensors. For comparison, measurements were also done using a portable, open-source instrument, OpenQCM. The OpenQCM instrument directly measures changes in resonance frequencies, making it ideal for biosensing experiments, which correlate changes in mass with changes in resonance frequencies. Comparison between resonance frequency measurements using VNA and OpenQCM exhibit low percentage difference 0.2%. This QCM sensor array has the potential of conducting real-time, point-of-care analyses for detection of biological molecules.